Green Jobs in the Green Transition as a Regulatory and Investment Strategy to Overcome Employment Disparities in the Conventional Economic Sector - Nurul Najwa Binti Jefrey; Desi Marlita Sitompul; Muhammad Fiqri Silalahi (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2026)
The green transition is considered Indonesia's development agenda in facing the environmental crisis, and at the same time, encouraging the performance of sustainable growth in the economy. Among the main tools of this transition is the creation of jobs that are expected to be able to provide decent work. Nonetheless, it can be seen that the creation of new jobs in Indonesia faces different structural barriers that limit this transition process. This study, by this thesis, seeks to interpret how new jobs perform during the transition to green. This research adopts a descriptive method that uses a qualitative approach using secondary data obtained from government documents, global organization reports, and scientific literature. This study will use the process of reduction, categorization, and interpretation of the data obtained. The findings of the study show that the potential for green jobs in the fields of renewable energy, waste management, and sustainable agriculture has not been fully utilized due to low skills in green jobs, fragmentation of labor regulations, and concentration of green investment in certain areas. The findings of this study confirm that without integrated policymaking, the green transition can exacerbate structural inequalities. The importance of this paper focuses on the role of the just transition approach in the formulation of green work policies in Indonesia.